GEJALA PERUBAHAN IKLIM, DAMPAK DAN STRATEGI ADAPTASINYA PADA WILAYAH DAN KOMUNITAS NELAYAN DI KECAMATAN BLUTO, KABUPATEN SUMENEP - Indrawasih, Ratna (P2KK LIPI, 2012)
This article discusses the results of research in Sumenep, East Java Province. The purpose of the research is to understand the community perceptions on natural conditions and symptons related to climate change; to understand the impact of the climate change to the coastal environmental and livelihood activities; and to identify how the adaptations made strategy developed on the economic activity. The study was using a qualitative approach. Collecting data was carried out through in-depth interviews with the help of an interview guide. Purposive selection of informants and snowball step is then performed. The results showed that climate change and its impacts have been felt by the people in the District of Bluto, even though they do not understand that the time shift transition seasons, the rainy season to the dry season is the symptoms of climate change. The impacts felt by people such as reduced income to meet their economic needs, adding to the reduction in yield from the sea as a fisherman, was also unable to obtain additional land, because they can not grow tobacco. An adaption strategy undertaken by fishermen is to do seaweed farming and the farmers to grow herbal chilly. Keywords: climate change, impact, strategy of adaptation, fisherman